Islam’s Combat of Racism as Evidenced by Al-Qur’an and Hadith - Latef, Khadiga Musa (ADDIN, 2020)
A few months ago the USA was overcome by nationwide protests that continue to this day; these protests expanded internationally. The protests were sparked by the death of George Floyd, an unconvict African-American man. The incident indicates that racism is still prevalent. This article shall argue that Islam condemns racism and that it came with a plan to end slavery, which was very popular in pre-Islamic days and also to end racist action in all its forms. According to Islamic teaching, racism should have disappeared fourteen centuries ago. This article shall present Qur’anic verses and Prophetic hadith to the effect that in Islam all people are supposed to live in harmony and equality. There should be no discrimination on bases of race, money, skin color or religious believes.